A High‐Performance Sound Insulation Component for Filter Capacitors Based on Coiled‐up Acoustic Metamaterials. Issue 14 (1st June 2022) - Lin, Qinhao; Di, Guoqing
Abstract : In the light of the spectrum characteristics of filter capacitor noise, a high‐performance sound insulation component (HSIC) based on coiled‐up acoustic metamaterials is developed. By efficiently absorbing harmonic components whose acoustic energy is predominant, HSIC can insulate the middle‐ and low‐frequency noise radiated by filter capacitors significantly. Simulated results show that under the excitation of a normal incident sound wave, the sound transmission loss of HSIC is 8.0, 7.0, 6.9, and 4.3 dB higher than that of a homogeneous panel with same area density (HPSAD) at the frequencies of 400, 500, 600, and 700 Hz, respectively. The transmission loss of HSIC for filter capacitor noise is 6.4 dB(A) higher than that of HPSAD. Experimental results show that under the excitation of a diffuse sound field, HSIC still has an excellent sound insulation performance and the transmission loss for filter capacitor noise can increase by 4.5 dB(A). Furthermore, an impedance analysis and a complex frequency plane analysis are conducted to elucidate the sound insulation and absorption mechanism of HSIC. Abstract : In the light of the spectrum characteristics of filter capacitor noise, a high‐performance sound insulation component (HSIC) based on coiled‐up acoustic metamaterials is developed. By efficiently absorbing its main harmonic components, HSIC can insulate the noise of filter capacitor significantly, which is 4.5 dB(A) higher than that of a homogeneous panel with same area density.